The Effect of Hypnotherapy on Pain Intensity in Postoperative Patients: A Systematic Review - Yuniasti, Risna Devi; Upoyo, Arif Setyo; Taufik, Agis (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Pain is a common problem in patients undergoing surgery. The constant postoperative acute pain can affect the physiological and psychological aspects of the patient.Objective: Non-pharmacological therapy is widely used for the treatment of chronic pain. Non-pharmacological therapy needs to be developed in acute postoperative pain due to concerns about the side effects of pharmacological treatment. There is non-pharmacological management that effectively reduces pain intensity, namely hypnotherapy.Methods: The systematic search for this review used the Google Scholar database, Directory of Open Access Journal (DOAJ), ProQuest, and PubMed using keywords (Hypnosis OR Hypnotism OR Hypnoanalysis OR Hypnotherapy OR Hypnotherapies OR Mesmerism) AND (Post-surgical Pain OR Post surgical Pain OR Postsurgical Pain OR Post-operative Pain OR Post operative Pain OR Post-operative Pains OR Postoperative Pain OR Acute Postoperative Pain OR Acute Post-operative Pain OR Acute Post operative Pain). The quality of journals was assessed using the Critical Appraisal Skills Program (CASP) instrument. The synthesis method used was narrative synthesis (narrative synthesis).Results: 10 articles were fully reviewed from 2010-2020. The visualization technique with rapid conversational induction has the best effect than other techniques. The most effective way of conveying suggestions is indirect with a permissive approach. The study results showed that hypnotherapy tended to reduce postoperative pain in minor surgical procedures than in major surgeries.Conclusion: Hypnotherapy affects reducing the pain intensity of postoperative patients. The results of this study recommend that hypnotherapy suggestions and pain measures must be tailored to the patient's condition.